PENGEMBANGAN MEDIA VIDEO ANIMASI POWTOON UNTUK PEMBELAJARAN PENDIDIKAN PANCASILA ELEMEN NKRI DI KELAS V SEKOLAH DASAR - Ocfa Chanda SP, Ryan; Reinita; Desyandri; Shilfia Iraqi, Hana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Pancasila Education instruction in elementary schools—specifically regarding the Unitary State of the Republic of Indonesia (NKRI) element—often relies on conventional media, which fails to adequately foster student engagement and learning motivation. This study aimed to develop a Powtoon-based animated video medium covering the topic "Recognizing Regional Characteristics" that is valid, practical, and effective for use in Grade V elementary school classrooms. A mixed-methods approach was employed using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Trial subjects included Grade V students from two trial schools (SDN 02 Kampung Olo and SDN 19 Kampung Olo) and one research school (SDN 20 Kurao Pagang) within Cluster I, Nanggalo District, Padang City. Data were collected through observations, interviews, expert validation questionnaires, teacher and student practicality questionnaires, and pre- and post-tests, followed by descriptive quantitative and qualitative analysis. The results indicated that the media was highly valid based on assessments by subject matter experts (98.33%), linguists (97.5%), and media experts (100%). Practicality testing at the trial schools yielded a "highly practical" rating based on teacher (94%) and student (94.5%) responses. Effectiveness testing showed an increase in average student scores from 62.17 (pre-test) to 88.26 (post-test), with a learning mastery rate of 91.30% at the trial schools and 91.67% at the research school; both results fell into the "highly effective" category. It is concluded that the Powtoon animated video is a suitable alternative medium for teaching the NKRI element of Pancasila Education in elementary schools.